1998
DOI: 10.1016/s0735-1097(98)00062-x
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcomes of Right Atrial Isomerism: A 26-Year Experience

Abstract: Right atrial isomerism continues to have an associated high mortality despite surgical innovations. Management of pulmonary vein obstruction remains a serious problem and is associated with high mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
262
1
15

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(289 citation statements)
references
References 29 publications
9
262
1
15
Order By: Relevance
“…1,3,6,7,20 In patients with right isomerism, the presence of an obstructed PV is an independent risk factor for a poor prognosis. 21 A previous study suggested that the presence of echocardiographically defined turbulence within the PVs after repair is associated with restenosis, 22 and another study reported that the size of the individual PVs was an important determinant of outcome in patients with TAPVC. 23 Although pediatric data on the outcome of intravascular stent implantation for pulmonary artery and systemic vein stenosis suggests an exceptionally high patency rate, stent procedures in children with congenital or post repair PV stenosis are frequently complicated by restenosis with neointimal proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…1,3,6,7,20 In patients with right isomerism, the presence of an obstructed PV is an independent risk factor for a poor prognosis. 21 A previous study suggested that the presence of echocardiographically defined turbulence within the PVs after repair is associated with restenosis, 22 and another study reported that the size of the individual PVs was an important determinant of outcome in patients with TAPVC. 23 Although pediatric data on the outcome of intravascular stent implantation for pulmonary artery and systemic vein stenosis suggests an exceptionally high patency rate, stent procedures in children with congenital or post repair PV stenosis are frequently complicated by restenosis with neointimal proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Higher preoperative mean PA pressure, asplenia syndrome and higher post-Fontan pulmonary artery pressure, were predictive of poor early outcome or Fontan take-down, while systemic AV valve incompetence reached borderline significance. A recent review of the Toronto experience showed that Fontan completion was achieved in only 22% patients with right atrial isomerism and single ventricle physiology 19 with 25% mortality. Actuarial survival for patients presenting after 1989 was 32% at 1 year, therefore implying that improvements in surgical techniques did not ameliorate early outcome.…”
Section: Discussionmentioning
confidence: 99%
“…149 The results for patients with right atrial isomerism are even more disappointing. 150 Although a Fontan operation can be carried out in some patients with right atrial isomerism with a mortality Ͻ10%, a cohort analysis showed that only 35% of all 91 patients seen at the Toronto Hospital for Sick Children with right atrial isomerism from 1970 to 1996 were alive at 5 years. Similar results have been published by Sadiq and his colleagues, reviewing the Birmingham Children's Hospital, 153 and from the review by Gaynor and his colleagues of the Children's Hospital of Philadelphia.…”
Section: Outcome Analysis In Congenital Heart Diseasementioning
confidence: 99%